Evaluation of the occlusion vertical dimension of complete dentures after microwave disinfection - Basso, Michael F. M. [UNESP]; Giampaolo, Eunice T. [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2012)
Objectives: An increase in occlusal vertical dimension (OVD) after microwave disinfection may result in the need for adjustments in the complete dentures. This in vitro study evaluated the increase in OVD of maxillary complete dentures submitted to microwave disinfection protocols.Material and methods: Thirty sets of complete dentures were evaluated as follows: Group 1-15 sets had the maxillary complete dentures submitted to microwave disinfection (650 W/ 3 min), once a week, for 4 weeks. Group 2-15 sets had the maxillary complete dentures submitted to microwave disinfection (650 W/ 3 min), three times a week, for 4 weeks. The vertical dimension was measured with a micrometre (in mm) before disinfection protocols (baseline readings) and after each week of disinfection. Data were analysed using Wilcoxon and Friedman tests (a = 0.05).Results: For Group 1, no significant difference was found between the increases in OVD and zero, and no significant difference was found between the weeks. For Group 2, the increases in OVD were significantly greater than zero, and the Friedman test showed that weeks 3 and 4 had significantly greater changes than week 1 and that week 4 had significantly greater change than week 2.Conclusion: Microwave disinfection only promoted significant increase in OVD in Group 2, in which the values increased progressively.
Keywords: complete denture; vertical dimension; microwaves; disinfection; acrylic resin